KEPUTUSAN PETANI KARET BERALIH KE USAHATANI SINGKONG DI KECAMATAN WAY SERDANG KABUPATEN MESUJI - Santi, Putu Yogi; Prasmatiwi, Fembriarti Erry; Situmorang, Suriaty (Lampung University, 2024)
This study aimed to calculate the income of rubber and cassava farming per hectare and to analyze the factors influencing rubber farmers' decision to switch to cassava farming. The research location was intentionally chosen in Raja Boga Village and Bukoposo Village, Way Serdang Subdistrict, Mesuji District, considering the phenomenon of a shift from rubber to cassava farming happened in this area. The sampling method was non-probability sampling with purposive sampling technique. The sample selection was based on specific criteria, i.e. rubber farmers who switched to cassava and those who did not, with a total of 35 farmers in each category. Data collection took place from March to April 2023. The data analysis methods were income analysis and independent sample t-test analysis conducted to address the first objective and logistic regression analysis (logit) conducted to address the second objective. The results of this research showed that the average income from rubber farming per hectare was Rp11,136,084.39, while the income from cassava farming per hectare was Rp17,111,593.03. There was a significant difference between the incomes of rubber and it of cassava farming. Factors significantly influencing the likelihood of farmers switching from rubber to cassava farming were farming income, family dependent, and the duration of farmers' education. Key words: Income, Switching of farming, Rubber, Cassava